2014
DOI: 10.1007/s10646-014-1348-x
|View full text |Cite
|
Sign up to set email alerts
|

CYP-dependent induction of glutathione S-transferase in Daphnia similis exposed to a disperse azo dye

Abstract: Disperse Red 1 (DR1) is an azo dye that can reach the aquatic environment through the discharge of textile industrial wastewaters. It has been tested in Daphnia similis and shown to be highly toxic. Cytochrome P450 (CYP) is a class of enzymes involved in phase I of detoxification, while glutathione S-transferase (GST) are a class of phase II enzymes. No information about phase I or II dye metabolism in microcrustacea were found in the literature. In this study we identified CYP and GST enzymes involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
3
0
4
Order By: Relevance
“…GST and CAT were assessed to reflect the response of antioxidant enzymes to PFOS (G omez-Oliv an et al, 2014;Yu et al, 2014). While exposed to toxicants, the body produces oxidative stress and the balance of active oxygen is broken.…”
Section: Antioxidant and Neurological Responsesmentioning
confidence: 99%
“…GST and CAT were assessed to reflect the response of antioxidant enzymes to PFOS (G omez-Oliv an et al, 2014;Yu et al, 2014). While exposed to toxicants, the body produces oxidative stress and the balance of active oxygen is broken.…”
Section: Antioxidant and Neurological Responsesmentioning
confidence: 99%
“…CYP450 is one of the major phase I-type classes of biotransformation enzymes and converts xenobiotic compounds into water-soluble substances (Bonnafé et al, 2015). The relationship between the CYP450 enzyme and toxicity of xenobiotic chemicals to several insects has been studied previously and it has been found that the CYP450 genes were related to insecticide resistance (Dulbecco et al, 2018;Kaplanoglu et al, 2017;Nair et al, 2013;Tang et al, 2017;Yu et al, 2015). The members of the CYP4 family are frequently related to specialized biochemical pathways such as the biosynthesis of endogenous compounds and metabolism of pheromones (Xiong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Azo dyes also interact with enzymes in the liver, e.g. glutathione-stransferase (GST) and cytochrome P450 (CYP) involved in the conversion of xenobiotic compounds to facilitate their elimination [8]. Exposure to such toxic compounds as azo dyes may hamper the GST catalysis of the conjugation of glutathione (GSH) to a wide variety of endogenous and exogenous electrophilic compounds [9], thus leading to cell proliferation in the early stages of oncogenesis [10][11][12].…”
Section: Introductionmentioning
confidence: 99%